2019
DOI: 10.1038/s41598-019-41830-w
|View full text |Cite|
|
Sign up to set email alerts
|

Illumina sequencing of clinical samples for virus detection in a public health laboratory

Abstract: High-throughput sequencing (HTS) provides the opportunity, once a diagnostic result is obtained, to extract additional information from a virus-containing sample. Hence, it offers advantages over established quantitative amplification technology, such as quantitative PCR, particularly in a public health environment. At this early stage of its clinical application, there have been limited studies comparing HTS performance to that of the more established quantitative PCR technology for direct detection of viruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…RNA extracted from all six excreta samples collected from groups of experimentally infected mosquitoes were positive for either WNV KUN or RRV by RT-rtPCR, with mean (± standard error of the mean [SEM]) cycle threshold ( C T ) values of 26.3 ± 0.4 and 26.8 ± 1.0, respectively. Based on these results, six libraries were subsequently prepared and next-generation sequenced using the Illumina NextSeq platform ( 21 ). The mean (± SEM) numbers of raw reads obtained from the libraries from mosquitoes exposed to WNV KUN or RRV were 5, 877,227 ± 137,555 and 9,020,173 ± 515,578, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA extracted from all six excreta samples collected from groups of experimentally infected mosquitoes were positive for either WNV KUN or RRV by RT-rtPCR, with mean (± standard error of the mean [SEM]) cycle threshold ( C T ) values of 26.3 ± 0.4 and 26.8 ± 1.0, respectively. Based on these results, six libraries were subsequently prepared and next-generation sequenced using the Illumina NextSeq platform ( 21 ). The mean (± SEM) numbers of raw reads obtained from the libraries from mosquitoes exposed to WNV KUN or RRV were 5, 877,227 ± 137,555 and 9,020,173 ± 515,578, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Libraries were diluted to 1 nM, pooled, denatured and diluted to a final concentration of 1.2 pM. Paired-end sequencing was performed using the NextSeq platform (Illumina) using a NextSeq 500 Mid Output V2 kit (Illumina) (21).…”
Section: Methodsmentioning
confidence: 99%
“…A study comparing the diagnostic efficiency of NGS vs. gold standard real time PCR in 89 nasopharyngeal swabs reported a sensitivity of 78% and specificity of 80% for NGS (Thorburn et al, 2015). More recently, a NGS sensitivity of 92% compared to real time PCR was found when testing a range of 52 clinical samples, including 8 of fecal origin (Huang et al, 2019). Target enrichment for sequences of viruses infecting vertebrate organisms, using biotinylated capture probes as a front-end procedure of NGS-based metagenomic sequencing, provides an opportunity for sensitive, broad detection of viruses (Wylie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Now knowing the potential of DRS for strain level detection of pathogens as determined through this study as well as others [75], we next investigated the analytical sensitivity of PRRSV detection to determine its usefulness for obtaining reliable sequencing results. Previous research examining analytical sensitivity of next-generation sequencing has reported sensitivities that are similar or less sensitive than RT-qPCR [28,76], and the third-generation Oxford Nanopore DRS has previously shown a sensitivity of 1.89 × 10 7 viral copies in an influenza virus study [44]. Our results indicated that samples with a minimum of 10 4 to 10 6 viral copies, depending on the sample type, can be successfully sequenced to accurately identify strains after about 6 hours of sequencing.…”
Section: Discussionmentioning
confidence: 99%